Determinants of Catfish Production in Akwa Ibom State, Nigeria - U.A. Asa; Valerie A. Solomon (Journal of Basic & Applied Sciences, 2015)
The study ascertained the determinants of catfish production in Akwa Ibom State, Nigeria having ascertained from literature that greater improvement in catfish production can be achieved with a proper analysis that will lead to knowledge of the profitability of catfish production in the country. Ascertaining the factors influencing catfish production in Akwa Ibom State of Nigeria was done based on this line of thinking. Data obtained from one hundred and twenty catfish farmers in Akwa Ibom State using multi-stage sampling procedure were analysed using descriptive statistics, budgeting technique and multiple regression. Findings reveal that 79.17% of the respondents were males, with an average age of 41 years; and 80% of them having formal education. The average monthly income of the respondents was N 32, 500.50 and their average year of fishing experience was four years. Results show that catfish production was profitable in the study area yielding a net income of N 18,539,760.00. The costs of fingerlings, pond construction, feed/chemicals, as well as fishing experience and amount spent on salary/labour were the significant factors influencing catfish production in the study area. It is recommended, among others, that catfish farmers in the study area be encouraged to form co-operatives to enhance their ability to access necessary inputs such as feed/chemicals at a subsidized rate. This will lead to an increase in the total revenue earned from catfish production.